Pengenalan Konsep Diri sebagai Penumbuhan Keberanian (Penghilang Kecemasan) dalam Berbicara pada Mahasiswa - Radhiah, Radhiah; Syahriandi, Syahriandi; Mahsa, Masithah; Syardiansah, Syardiansah; Fakhrah, Fakhrah (Penerbit Widina, Widina Media Utama, 2025)
This community service program aims to foster students' courage to speak (eliminate anxiety) through self-concept recognition. Students' lack of courage in speaking is a phenomenon that often occurs in formal situations. Students feel afraid, anxious, embarrassed, and find it difficult to express information due to anxiety/fear of making a mistake. This guilt causes a lack of self-confidence. Students feel they will be judged or commented on later by the audience. In fact, the students have not made any mistakes and are not being judged. This feeling must be resolved so that it disappears. One way to do this is through self-concept recognition. Self-concept means encouraging oneself to be more capable of knowing oneself (self-evaluation). The process of self-recognition is expected to eliminate students' anxiety and thus foster students' courage in speaking. In the self-recognition process, this community service program uses the